2013
DOI: 10.1016/j.jspd.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Increase in Three-dimensional Spine Flexibility Following Sequential Ponte Osteotomies in a Cadaveric Model

Abstract: Sequential Ponte osteotomies increased range of motion in flexion, extension, and axial rotation, but not in lateral bending. These results suggest that the Ponte osteotomy may be appropriate when using derotational correction maneuvers, or to improve apical lordosis at the apex of curvature during posterior spinal fusion procedures. Although these techniques are effective in gaining correction for kyphotic deformities and rigid curvatures, they add time and blood loss to the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The use of the original Ponte osteotomy for the treatment of rigid AdIS has been well documented in the literature [10][11][12][13]. Clinical and cadaver studies have shown marked segmental flexibility in all three planes produced by Ponte osteotomy [22][23][24]. Therefore, the apical and the first cephalad and caudal segments were selected as the candidate region for Ponte osteotomy in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the original Ponte osteotomy for the treatment of rigid AdIS has been well documented in the literature [10][11][12][13]. Clinical and cadaver studies have shown marked segmental flexibility in all three planes produced by Ponte osteotomy [22][23][24]. Therefore, the apical and the first cephalad and caudal segments were selected as the candidate region for Ponte osteotomy in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the effect of the transfer in the cadaver specimens may not precisely reproduce the effect that may be seen in the clinical situation. However, adult specimens have been used in place of pediatric specimens in several published studies and have provided meaningful results [12,15,23]. Second, anatomic positioning of each specimen had to be approximated, and to minimize variability in the data, the same positioning method was used for each trial.…”
Section: Discussionmentioning
confidence: 99%
“…The software calculates the 3-D position for each marker and displays its coordinates in real time. This motion tracking system has an accuracy of 0.1 mm, a resolution of 0.01 mm at a distance of 2.25 m, and has been used in previous studies [4,23]. Motion-tracker flags were created by mounting four LED markers equidistant from the center of a 1.5-inch square plastic fixture, creating a noncollinear 1-inch-square arrangement.…”
Section: Methodsmentioning
confidence: 99%
“…However, cadaveric biomechanical evidence suggests that PCO have a small effect on the coronal flexibility of the thoracic spine but notable effect on the sagittal flexibility of the intact spine. 38 Resection of the posterior column tension band with PCOs transitions the axis of rotation anteriorly, detethers the posterior elements, and enables dorsal lengthening, all of which facilitates restoration of TK at the apical lordosis of the thoracic curve apex. Apical PCOs have been advocated as an integral component of the multimodal surgical approach to restore TK in hypokyphotic patients.…”
Section: Posterior Column Osteotomiesmentioning
confidence: 99%